Sequenciamento, montagem e anotação do genoma de um novo isolado de Leptospira borgpetersenii - Eslabão, Marcus Redü (2012)
Leptospirosis is a neglected zoonosis with global distribution. The disease is caused by pathogenic bacteria of the genus Leptospira, which affect humans and various domestic and wild animals, causing serious problems to human health and damage to livestock. The objective of this study was to determine the genome sequence of Leptospira borgpetersenii serogroup Ballum strain 4E, isolated from domestic mice (Mus musculus), one of the main reservoirs of this genus. The complete genome sequence was determined using SOLiDTM system, which generated over 85 million 50 bp reads. These reads were used to obtain scaffolds of the two chromosomes present in this organism through the ab initio sequence assembly with Velvet and Edena softwares and orientation of contigs with G4All software. With completion of the assembly process, the large chromosome was 3,071,053 bp, GC content of 40.58%, 36 tRNA, 4 rRNA and 2,908 open reading frames (ORF). The small chromosome has 305,940 bp, GC content of 40.25%, 277 ORFs, no tRNA or rRNA. A reduction in the large chromosome of 4E strain was observed compared to the large chromosome of L550 strain, where 99 genes of L550 strain are not present in the 4E strain and about 394 kb of non-coding region was also lost. The main hypothesis for this reduction is the effect of the presence of a large number of mobile genetic elements. Genome reduction has been observed in other strains of L. borgpetersenii. The Applied Biosystems SOLiD 4 method allowed determination of the genome sequence of L. borgpetersenii strain 4E, with wide coverage and accuracy. The ab initio assembly methods used allowed for complete utilization of the sequences generated.